CORELATIONAL SPATIOTEMPORAL ANALYSIS DENGUE HAEMORRAHAGIC FEVER (DHF) WITH SETTLEMENT CONDITION IN PALEMBANG CITY, INDONESIA - Mariana, .; Diora, Agita; Ismah, Zata; Irpani, Tri Hari; Cahyo, Rahardian Dwi; Singh, Mandeep Singh Mukand (LIFE: International Journal of Health and Life-Sciences, 2018)
Analysis with spatial method has an role important for describing the health problems between regions, and knowing the determinant of problem. However, the research of Dengue Hemorrhagic Fever (DHF) with this method was rarely founded in Palembang.The objective of this study was to determine identify the incidence of DHF through spatio-temporal, compared with population density, healty housing proportion and slums area in years 2009-2013.The study was observasional with ecological design. Secondary data got from data weekly reports Health Department Palembang City and reports Spatial and Housing Department. The data was processed into tabular and spatial. Spatial data was processed by using ArcView and GIS. Statistic corelation analysis with Spearman and Pearson analysis. Subjects research and unit analysis were all health centers in city (39 unit). The results is spatial distribution showed the high of DHF cases in Seberang Ilir area specially Centre area and Northern area. It was the area predominantly has many water reservoir. The high case of DHF (IR >50 per 100.000 population) shows at : population density areas (relation in year 2010 P=0.039, r=-0.332), and healty housing proportion (relation in year 2009 P=0.010 r=0.554; in year 2010P=0.007 r = 0.445; in year 2011 p=0.015 r = 0.404) and slum area P0.034**, r= -0.345.Temporally distribution showed the decrease of DHF cases during the last 5 years.Interventions of preventing DHF is needed in priority areas, that is in North and Centre area. Preferred improvement of water supply, Collaborative activity between GERTAK PSN DBD and PSN 60 minutes, Inviting cadres of middle and upper economic class society, and doing alert for 5-years cycle